Dilema Penegakan Hukum dan Ham : Kajian Kasus Pelanggaran oleh KKB-OPM dari Perspektif Hukum dan HAM - Anggelica Regina Simamora; Audy Luvena Junaedi; Alfiya Hasanah Ruhiyat; Claudia Larisa Sihaloho; Chelsea Merrysha Khana Gultom; Demak Angelina Sinaga; Keizya Aura Maharani; Winih Auraning Illahi; Mulyadi Mulyadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The conflict involving Armed Criminal Groups (KKB) in Papua presents a serious dilemma between law enforcement and the protection of human rights. On one hand, KKB’s actions—such as attacks on civilians and security personnel—are classified as gross human rights violations, posing threats to national security and obstructing regional development. On the other hand, law enforcement efforts by state authorities are often criticized for alleged human rights abuses, especially in military operations that may involve excessive use of force. This study aims to analyze the conflict from both legal and human rights perspectives using a normative juridical approach. The analysis is based on relevant legal frameworks, including the 1945 Constitution of the Republic of Indonesia and Law Number 39 of 1999 concerning Human Rights. The article proposes strategic measures to achieve a balanced resolution, such as inclusive dialogue with Papuan communities, human rights-based training for security forces, independent oversight of security operations, and adherence to humanitarian principles. These approaches are expected to foster stability and peace while ensuring the protection of human rights. Ultimately, this study emphasizes that the resolution of the Papua conflict must not rely solely on repressive measures but must also prioritize justice, humanity, and long-term sustainability.